THE EFFECT OF PROFESSIONAL WORK ETHICS ON DOCTOR’S COUNTERPRODUCTIVE WORK BEHAVIOUR AND LEADER-MEMBER EXCHANGE QUALITY AS MEDIATOR - Budiman,; Halimoon, Fatimah wati; Selamat, Mohd Nasir (International Journal of Psychosocial Rehabilitation, 2020)
Counterproductive work behaviour causes adverse effects towards organizational goal achievements, social and economic loss as well as an individual’s safety at work. However, research relating to factors influencing counterproductive behaviours are still limited. Therefore, this research attempts to test the direct influence of various factors professional work ethics and leader-member exchange quality towards counterproductive behaviour. At the same time, leader-follower relationship quality was also tested as mediator. professional work ethics was measured using The Multidimensional Work Ethic Profile (MWEP), leader-member exchange quality was measured by Multidimensional Instrumental Leader-Member Exchange (MDM-LMX) and counterproductive work behaviour was measured using the Counterproductive Work Behaviour-Checklist (CWBC). All questionnaires went through the process of a standard translation from English to the Indonesian language. Data was collected from N = 408 doctors working in a government hospital in Palembang city, South Sumatera of Indonesia and was analysed using Confirmatory Factor Analysis (CFA) and Structural Equation Modelling (SEM). Results of the SEM analysis showed professional work ethics contributed towards counterproductive work behaviour, followed leader-member exchange quality. This investigation further supported that there is a negative indirect and notable effect factor professional work ethics on counterproductive work behaviour through leadermember exchange quality as mediators. Further, predictor factors, namely professional work ethics, added 28% and leader-member exchange quality gave 23% on variance counterproductive work behaviour. All factors contributed 15% of variance towards counterproductive work behaviour. In the second model, professional work ethics contributed 40% of the variance to leader-member exchange quality. However, leader-member exchange quality was found to be a significant mediator in the relationship. In conclusion, work ethics was found to be the most important factor in influencing counterproductive work behaviour and leader-member exchange quality. Therefore, employers should provide appropriate ethic codes and guidelines related to professional medical work ethics as well as an intervention on behaviour change towards integrity. Besides that, coaching programs to increase group cohesion and teamwork between the young and experienced doctors should be conducted as well as remedial training to teamwork to ensure high productivity among doctors working in government hospitals in Palembang city, South Sumatera of Indonesia.